2011
DOI: 10.3727/096368910x544915
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Stimulation Nurtures Endogenous Neurogenesis and Angiogenesis in Chronic-Phase Ischemic Stroke Rats

Abstract: Deep brain stimulation (DBS) is used to treat a variety of neurological disorders including Parkinson's disease. In this study, we explored the effects of striatal stimulation (SS) in a rat model of chronic-phase ischemic stroke. The stimulation electrode was implanted into the ischemic penumbra at 1 month after middle cerebral artery occlusion (MCAO) and thereafter continuously delivered SS over a period of 1 week. Rats were evaluated behaviorally coupled with neuroradiological assessment of the infarct volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 77 publications
1
30
0
Order By: Relevance
“…Similar reports have demonstrated cross‐talk between secreted factors (e.g., apoptosis, inflammation, oxidative stress) (; Brill et al, 2009; Chapman et al, 2015; Lu, Jones, Snyder, & Tuszynski, 2003; Zhang et al, 2015) and neurogenesis following brain insults, including stroke (Kernie and Parent, 2010; Yamashita et al, 2006). We (Hara et al, 2007; Morimoto et al, 2011; Tajiri et al, 2013), and others, have shown the important contribution of neurogenic factors in stroke brain remodeling (Jablonska et al, 2016; Rosell et al, 2013; Seo et al, 2014; Venna, Xu, Doran, Patrizz, & McCullough, 2014). Altogether, these results allude to host neurogenesis and its secreted neurogenic factors as key therapeutic targets of NSI‐189 in affording behavioral and neurostructural benefits in stroke.…”
Section: Discussionmentioning
confidence: 87%
“…Similar reports have demonstrated cross‐talk between secreted factors (e.g., apoptosis, inflammation, oxidative stress) (; Brill et al, 2009; Chapman et al, 2015; Lu, Jones, Snyder, & Tuszynski, 2003; Zhang et al, 2015) and neurogenesis following brain insults, including stroke (Kernie and Parent, 2010; Yamashita et al, 2006). We (Hara et al, 2007; Morimoto et al, 2011; Tajiri et al, 2013), and others, have shown the important contribution of neurogenic factors in stroke brain remodeling (Jablonska et al, 2016; Rosell et al, 2013; Seo et al, 2014; Venna, Xu, Doran, Patrizz, & McCullough, 2014). Altogether, these results allude to host neurogenesis and its secreted neurogenic factors as key therapeutic targets of NSI‐189 in affording behavioral and neurostructural benefits in stroke.…”
Section: Discussionmentioning
confidence: 87%
“…This suggests that electrical stimulation increased the expression of SDF-1α a few days after ischemic stroke. While electrical simulation enhances expression of various cytokines like a vascular endothelial growth factor (VEGF), Glial cell line-derived neurotrophic factor (GDNF) and brain-derived neurotrophic factor (BDNF) [18, 41], there are no reports about the effect of electrostimulation on expression of SDF-1α in the brain. Interestingly, the expression of SDF-1α was significantly increased in the anal sphincter of rats immediately after 1 hour of electrical simulation [42].…”
Section: Discussionmentioning
confidence: 99%
“…Striatal stimulation also offers neuroprotection in cerebral ischemia, but via alternate mechanisms involving neural repair. Striatal stimulation enhances migration of neural progenitor cells towards the penumbra and their subsequent differentiation into neurons [80]. In acute models, cortical stimulation may operate by upregulating neurotrophic and angiogenic factors in tandem with suppression of apoptotic cell death [81].…”
Section: Differentiating Between Short-and Long-term Mechanisms Of Comentioning
confidence: 99%